Evaluation of Genetic Diversity of Advanced Pigeonpea [Cajanus cajan (L.) Millspaugh] Interspecific Derivatives Using Mahalanobis D2 and Selection of Elite Lines Using Multi-Trait Genotype-Ideotype Distance Index - Chauhan, Nilesh; Singh, Inderjit; Kumar, Harish; Vij, Suruchi (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during kharif (May–November, 2022) season at the field experimental area of the Department of Plant Breeding and Genetics, Punjab Agricultural University, Ludhiana and at Regional Research Station, Faridkot, Punjab, India to assess the genetic diversity of 40 advanced BC1F8/F9 pigeonpea interspecific derivatives derived from a cross between Cajanus scarabaeoides (L.) Thouars (ICP 15683) and C. cajan (L.) Millspaugh (ICPL 20329) using Mahalanobis D2. The data for 11 key productivity traits was statistically analysed using R software. The derivatives were grouped into five clusters. Intra-cluster distances varied from 0.00 (Cluster V) to 107.40 (Cluster IV), while inter-cluster distances ranged from 123.49 (Cluster II and V) to 511.00 (Cluster IV and V). The derivatives in the present study were mostly divergent for harvest index, pods plant-1, primary branches and seed yield plant-1. The MGIDI index was remarkably efficient in selecting superior derivatives, resulting in desired gains across numerous traits. The MGIDI index highlighted six high-performing genotypes—AL 2581, AL 2611, AL 2577, AL 2613, AL 2606 and AL 2597. This research laid the groundwork for forthcoming pigeonpea hybridization initiatives, enabling the selection of parents based on both diverse genetic backgrounds and specific traits. The study suggested a targeted screening of lines within promising clusters for utilization in ongoing breeding programs, facilitating the development of valuable populations and hybrids.